Sarekat Islam sebagai Kelanjutan Boedi Oetomo - Achdian, Andi (Jurnal Sejarah, 2017)
This paper is an effort to offer new information and analyses on the early periods of the so-called Indonesian national awakening in the first decade of the twentieth century. By taking into account the development of early nationalist movement in the colonial city of Surabaya, this paper showed an interesting but neglected role of H.O.S Tjokroaminoto as the leader of Boedi Oetomo chapter in Surabaya. Tjokroaminoto's role throws into a light the bridge that linked BO to SI movement. This paper argues rather than representing a separate development in the history of Indonesia's national movement, SI was in fact a continuation of BO movement with ideals about the progress and emancipation of native society that was common among the new generation of Indonesia's educated elite the time.